PROSTHETIC REHABILITATION WITH CERAMIC RESTORATIONS IN THE ANTERIOR REGION FOLLOWING ORTHODONTIC TREATMENT - Alexandra-Ioana Danila; Dana Cristina Bratu; Dan Lolos; Roxana Oancea; Mihai Rominu; Sorin Gheorghe Mihali (Romanian Journal of Oral Rehabilitation)
This study explores the survival rates and complications associated with zirconia restorations veneered with feldspathic ceramic in patients who had been diagnosed by an orthodontist with spacing issues. All patients had previously undergone orthodontic treatment to improve aesthetics after their teeth had been properly aligned. As a result, these cases were addressed through prosthetic solutions. The study included 18 patients, with 11 pairs of restorations for females and 7 for males, all targeting the anterior region to correct diastema. The restorations were followed over a two-year period, with check-ups scheduled every six months. Of the 18 restorations, 10 experienced chipping, primarily at the incisal edges. Additionally, two cases showed a recurrence of diastema due to non-compliance with wearing their Hawley retainers. Interestingly, the failure rate was higher in female patients, indicating a potential link between gender and the durability of the restorations. Despite these challenges, the restorations that suffered chipping could be successfully repaired, which proved to be a significant benefit. These findings highlight the importance of regular follow-up visits to ensure the longevity of the restorations and to inform future treatment planning.